2018
DOI: 10.22435/bpk.v46i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Potensial Reaksi Kusta Pada Etnis Asli di Dua Kantong Kusta – Papua

Abstract: Abstract Papua and West Papua are two provinces in Indonesia with high rate of leprosy number. One of the problems in leprosy management is the emergence of leprosy reactions. The purpose of this study was to identified  potential risk factors affecting to leprosy reaction among indigenous people in two  leprosy pockets in Papua and West Papua. Cross-sectional studies were conducted in 10 months (February-November 2018) in Jayapura City and Bintuni District, by interview using questionnaire and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(32 reference statements)
1
0
0
1
Order By: Relevance
“…Subject characteristics based on the length of illness has average 15 months in the control group and 8 months in the treatment group. These results in line with other studies, which state that the most extended duration of patients suffering from leprosy is within one year, which is 79.5% (Antonius et al, 2018). Research by Nazli et al (2021) reported that the length of leprosy in the group >12 months in their study was 45.7%.…”
Section: Discussionsupporting
confidence: 90%
“…Subject characteristics based on the length of illness has average 15 months in the control group and 8 months in the treatment group. These results in line with other studies, which state that the most extended duration of patients suffering from leprosy is within one year, which is 79.5% (Antonius et al, 2018). Research by Nazli et al (2021) reported that the length of leprosy in the group >12 months in their study was 45.7%.…”
Section: Discussionsupporting
confidence: 90%
“…Reaksi kusta dapat terjadi sebelum, selama, atau setelah pengobatan Multi Drug Therapy (MDT). 6 Reaksi kusta merupakan penyebab terbesar kerusakan saraf pada penderita kusta. Pada reaksi kusta, faktor risiko terjadinya penyakit ini antara lain, umur saat didiagnosis kusta >15 tahun, lama sakit lebih dari 1 tahun, terdapat kelelahan fisik, dan perubahan hidup tertentu pada wanita seperti pubertas, kehamilan, atau menyusui.…”
Section: Pendahuluanunclassified